Toward a Definition of Transnational Girlhood. Issue 2 (1st July 2019) - Vanner, Catherine
Abstract : In this article, I join a conversation about the definition and value of the term transnational girlhood. After surveying the fields of transnationalism, transnational feminism, and girlhood studies, I reflect on the representation of girls who act or are discussed as transnational figures. I critique the use of the term, analyze movements that connect girls across borders, and close by identifying four features of transnational girlhood: cross-border connections based on girls' localized lived experiences; intersectional analysis that prioritizes the voices of girls from the Global South who, traditionally, have had fewer opportunities to speak than their Global North counterparts; recognition of girls' agency and the structural constraints, including global structures such as colonialism, international development, and transnational capitalism, in which they operate; and a global agenda for change.